2016
DOI: 10.7322/jhgd.110024
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the development of preterm children at four and eight months of corrected gestational age

Abstract: Introduction: The big advances in perinatal care have resulted in longer survival of newborns with lower birth weight. However, these children are at high risk for developmental alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…In the first logistic regression model of this study, BPD was identified as a risk factor for language development. Although, in the final logistic regression model, this variable does not demonstrate statistical significance, studies have already shown that BPD may have impact on development, associating with cognitive impairments (8,19) . There were also reports that children who progressed with BPD had deficit in intelligence, reading, mathematics and fine motor skills, when compared to those born full-term and premature without BPD (28) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the first logistic regression model of this study, BPD was identified as a risk factor for language development. Although, in the final logistic regression model, this variable does not demonstrate statistical significance, studies have already shown that BPD may have impact on development, associating with cognitive impairments (8,19) . There were also reports that children who progressed with BPD had deficit in intelligence, reading, mathematics and fine motor skills, when compared to those born full-term and premature without BPD (28) .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies in the field of child development have investigated the association between preterm birth and handicap in this development, comprising sensory, growth, language and / or learning gaps (2,3,4,5,6,7,8,9,10,11) . However, such risk is not due to prematurity per se, but can be attributed to the adverse conditions associated with preterm birth, which may evolve to nervous system damage (5,8,19,21,22) . The aim of this study was to assess the adversities to which children born under the complex condition of prematurity are exposed, determining which factors are involved in the language development delay.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations